2002
DOI: 10.1002/sia.1255
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale bimetallic catalysts: are they really bimetallic?

Abstract: The existence of bimetallic particles (and their reducibility and location on/or in the support) in Ru-Co/NaY and Pt-Co/NaY samples has been studied by in situ X-ray adsorption spectroscopy (XAS). It is established that in Ru-Co/NaY the monometallic clusters maintain their identity, whereas in Pt-Co/NaY the existence of small bimetallic particles can be established. In both cases the results are supported by other techniques, such as XPS and temperature-programmed reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The Au/Pd system was chosen because of its remarkable. catalytic properties for many fine chemical fabrications, deep hydrogenation reactions and Co oxidation [4]. Figure 1a shows a HA-ADF image of a nanoparticle of AuPd (1:1 in atomic composition) in which surface roughness is observed; that roughness is consistent with the DFT calculation of a similar particle, shown in Fig.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…The Au/Pd system was chosen because of its remarkable. catalytic properties for many fine chemical fabrications, deep hydrogenation reactions and Co oxidation [4]. Figure 1a shows a HA-ADF image of a nanoparticle of AuPd (1:1 in atomic composition) in which surface roughness is observed; that roughness is consistent with the DFT calculation of a similar particle, shown in Fig.…”
supporting
confidence: 73%
“…optical properties, catalytic properties, electronic properties, etc. [3][4][5][6][7]. When two or more different elements compose one nanoparticle, the differences in atomic radii are going to influence the way the atoms accommodate.…”
mentioning
confidence: 99%
“…There have been numerous efforts to synthesize uniform bimetallic particles spanning a range of compositions; however, most of these studies have shown that although it is possible to prepare binary particles with uniform sizes/shapes and specific compositions, it is extremely difficult to control the uniformity on a particle-by-particle basis [4][5][6][7][8][9][10][11][12][13][14][15]. The composition from particle to particle can vary as much as 0-50% mole fraction with further uncertainty regarding whether the particle is of the ''alloy'' or ''core-shell'' type.…”
Section: Introductionmentioning
confidence: 99%
“…While not as easily accessible as other techniques, synchrotron-based X-ray techniques are very promising for fulfilling these criteria. For example, X-ray absorption (EXAFS) has been applied successfully to characterize bimetallic catalysts. , …”
Section: Introductionmentioning
confidence: 99%